Transitivity, paradigmatic choices, and thought presentation: A stylistic analysis of Joyce’s Eveline - Cunanan, Bonifacio Tala (Universitas Pendidikan Indonesia, 2019)
This paper shows how analyzing styles in fiction can be achieved in three ways: an in-depth examination of the role assignment of lexico-syntactic features, categorization of the choices in combining words, and examination of strategies in presenting characters’ perspectives. It offers ways on how to guide students in English as a second language (ESL) in analyzing and appreciating English fiction. It aims to equip them with language tools in evaluating a writer’s intended and desired aesthetic effects by using chosen linguistic features. To achieve this objective, this paper applies M.A.K. Halliday’s systemic-functional grammatical model illustrating how language works in Joyce’s Eveline, a short story. Specifically, this paper shows how EFL or ESL students can acquire a deeper appreciation of the worldview, perspective, or point of view of the author and his characters. Also, it illustrates how they may have a deeper appreciation of the craft, originality, and ingenuity of an author. Moreover, it demonstrates how using different techniques in speech and thought presentation could be made accessible by showing how rendering thoughts, feelings, and expressions can offer new perceptions and appreciations of what seems to be habitualized and ineffectual.